Evaluation of the relationship between vitamin D deficiency and microalbuminuria, glycaemic control, lipid profile in patients with type 2 diabetes mellitus - Yuksel Salduz, Zeyneb Irem; Ozder , Aclan (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the relationship of vitamin D deficiency with microalbuminuria, glycaemia and lipid profile in type 2 diabetes mellitus patients. Method: The retrospective, clinical study was conducted at Family Medicine outpatient clinics of Istanbul Bezmialem Vakif University, Faculty of Medicine Hospital, Turkiye, and comprised data between July 1 and December 31, 2019 related to adult type 2 diabetes patients. Data was classified according to vitamin D levels; <20ng/mL in group 1, and >20ng/mL in group 2. Microalbuminuria, glycaemia and lipid parameters were compared between the groups. Data was analysed using SPSS 28. Results: Of the 148 patients with mean age 56.58±9.76 years, 78(52.7%) were female and 70(47.3%) were male. The mean vitamin D level was 22.81±17.85ng/mL, with 76(%) patients in group 1 and 72(%) in group 2. The mean level of glycated haemoglobin was 7.57±1.66%. Total cholesterol, low-density lipoprotein cholesterol, lymphocyte and urine microalbumin/creatinine ratio as well as glycated haemoglobin levels were significantly higher in group 1 patients than those in group 2 (p<0.05). Vitamin D levels were significantly negatively associated with glycated haemoglobin and total cholesterol (p>0.05). Conclusion: Lower vitamin D levels were associated with poor glycaemic control, lipid dysregulation, and higher microalbuminuria, suggesting potential roles in glucose metabolism, inflammation and kidney function. Key Words: HbA1c, Microalbuminuria, Primary care, Type 2 diabetes mellitus, Vitamin D.